A COMBINED DATA STORAGE WITH ENCRYPTION AND KEYWORD BASED DATA RETRIEVAL USING SCDS-TM MODEL IN CLOUD - Divya, S.V.; Shaji, R.S.; Venkadesh, P. (Malaysian Journal of Computer Science, 2019)
With the hasty growth of the Internet technologies and the need for increased computational methods, cloud computing has become a new paradigm in the business and IT endeavors. This technology facilitates the enterprises to move their confidential data into the cloud, where their data is stored in a remote data centers and accessed via the internet. These resources are controlled by third parties who may not be trustworthy and provide adequate data security. While this technology has many benefits, the security issues also increases. Various methods have been proposed for designing a secure cloud storage system.However many of the prior works suffers from security, confidentiality, and integrity issues that limit the functionalities of the storage system. Moreover, the existing schemes suffers delay due to the lack of online verification, and increasein the communication cost as data is retrieved back to the owner for every request made by the user. Hence it remains a challenge for constructing an efficient data storage and data retrieval. In this paper, we present the development of a secure and efficient cloud storage system, â€œSCDS-TMâ€ that supports data confidentiality, data integrity, and data retrieval functionalities. With the use of Elliptic Curve Cryptography and storage correctness proof, weovercame the data confidentiality and data integrity issues. In order to augment the data retrieval functionality, we exploited a keyword search method called â€œcoordinate matchingâ€ technique of capturing the related documents based upon the search query.The performance of the proposed method is analyzed based on various factors such as communication overhead,data transfer rate, query execution time, data security level, probability ratio and precision ratio.Thorough analysis of scrutinizing the privacy and efficiency allow our proposed method to be secure, efficient and offers a higher level of security with low communication overhead.